DESAIN SISTEM ELEKTRODEPOSISI UNTUK PROSES PELAPISAN NITIALN PADA SUBSTRAT TUNGSTEN KARBIDA - Maulidatul Khasanah; Esmar Budi; Riser Fahdiran (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Electrodeposition of Ni-based composite films on metal is subjected to improve its wear and corrosion resistances. Electrodeposited Ni-TiAlN composite film on tungsten carbide rod as substrate has been investigated. Amount of 6 gr/liter of TiN and AlN powders were added into the electrolyte solution that consists of 0.38 M Ni2SO4.6H2O, 0.17 M NiCl2.6H2O, 0.49 M H3BO3 and 0,06 gr/l Sodium Dodecyl Sulfat (SDS). The experiment was performed with autonomous electrodeposition system because the device completed with potensiostat is expensive. Electrodeposiyon system is consist of power suplly, cable, resistor, electrolyte solution, and electrode. Electrodeposition was do in current of 3mA for about 25 minutes. The purpose of this experiment to find the composite film composition and morphology by using electrodeposition. Keywords: Ni-TiAlN composite film, electrodeposition, desain of electrodeposition system.